Primary alveolar rhabdomyosarcoma of the bone: two cases and review of the literature. Issue 1 (December 2016) - Balogh, Petra; Bánusz, Rita; Csóka, Monika; Váradi, Zsófia; Varga, Edit; Sápi, Zoltán
Abstract Background Rhabdomyosarcoma (RMS) is a malignant tumor of mesenchymal origin and comprises the largest category of soft-tissue sarcomas both in children and adolescents. From a pediatric oncology point of view, RMS has traditionally been classified into alveolar (ARMS) and embryonal (ERMS) subtypes. The anatomical localization of the tumor may vary, but commonly involve the head/neck regions, male and female urogenital tract or the trunk and extremities. Case presentation Here, we report two challenging cases involving 17- and 9-years-olds males where diffuse and multiplex bone lesions suggested either a hematological disease or a primary bone tumor (mesenchymal chondrosarcoma). Biopsies, proved a massive infiltration of the bone marrow cavity with rhabdomyosarcoma. In both cases, the ARMS subtype was confirmed using FOXO1 break-apart probes (FISH). Radiological examination could not identify primary soft tissue component in any localization at the time of diagnosis in either cases. Conclusions Primary alveolar rhabdomyosarcoma of the bone as a subtype of ARMS, seems to be a distinct clinico-pathological entity with challenging diagnostic difficulties and different, yet better, biological behavior in comparison to soft tissue ARMS. However, it is difficult to be characterized or predict its prognosis and long-term survival as only sporadic cases (four) were reported so far.